2018
DOI: 10.46568/jssh.v57i2.31
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oil Prices on Stock Returns: Evidence From Pakistan’s Stock Market

Abstract: Very few studies have investigated the movement in stock returns that result due to changes in oil prices. In recent years due to cooling down of China, unveiled oil reserves of Iran, decreasing demand worldwide and discovery of shale gases the world has experienced a large fall in the oil prices. These changes are also affecting performance of manufacturing and other associated companies in countries all over the world. Pakistan has also been affected by these changes in many ways. Especially, the returns on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There are several studies from some researchers for the relationship between crude oil price and stock markets in various countries, such as Hamilton (1983), Kaneko & Lee (1995); Kang, Ratti, & Vespignani (2016); and Killian & Park (2009) in the US; Masih, Peters, & De Mello (2010) in South Korea; Hasan & Ratti (2012) in Australia; Olsen & Henriz (2014) in the OECD countries; Najaf & Najaf (2016) in Pakistan and Malaysia; and Atiq & Farhan (2019) in Pakistan. These studies conclude that oil price changes have negative effects on the stock market returns.…”
Section: Figure 1 the Movements Of Bop And Several Stock Market Indicesmentioning
confidence: 99%
“…There are several studies from some researchers for the relationship between crude oil price and stock markets in various countries, such as Hamilton (1983), Kaneko & Lee (1995); Kang, Ratti, & Vespignani (2016); and Killian & Park (2009) in the US; Masih, Peters, & De Mello (2010) in South Korea; Hasan & Ratti (2012) in Australia; Olsen & Henriz (2014) in the OECD countries; Najaf & Najaf (2016) in Pakistan and Malaysia; and Atiq & Farhan (2019) in Pakistan. These studies conclude that oil price changes have negative effects on the stock market returns.…”
Section: Figure 1 the Movements Of Bop And Several Stock Market Indicesmentioning
confidence: 99%
“…Lastly, the effect of oil prices was also determined to be significant in the short and long term. It has also been supported in the study of Atiq and Farhan (2018) that prices of oil globally have a high impact on the country's economic prosperity and development that influence the stock returns.…”
Section: Bound Testingmentioning
confidence: 93%
“…The developments of the energy market that include crude oil, gas, coal, and other elements or utilities are many factors that impact energy utilities. Prices of oil globally have a high impact on the country's economic prosperity and development that influence the stock returns (Atiq & Farhan, 2018). H5: There is a positive impact of the Oil prices on the stock returns at the Netherlands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some countries such as China observed that their growth rate improved while Japan was in recession, and European countries such as Germany saw that their economic growth was declining, these being the main reasons that are considered responsible for the reduction in oil prices. Along with the movements in the supply and demand of oil price, the whole world has also opened up to the position of environmental friendliness and efficient lifestyle because crude oil has been substituted with biofuel (Atiq et al 2018).…”
Section: Introductionmentioning
confidence: 99%